Teaching and Learning History. - Timmins, Geoff (Teaching & Learning the Humanities Series., 2005)
This book, informed by exceptionally wide inquiry into current history teaching practices in the English-speaking world, is a real achievement. The authors convey current context and challenges with great insight, and they move through possibilities in sequencing, content, skills and assessment, without strident comment, extending our knowledge of options and pitfalls in the process' - Peter N. Stearns, Provost, George Mason University. 'Comprehensive, persuasive, and at all times accessible in style and argument, this text both encourages and empowers university historians to review and enhan.